Clinical course of chronic suppurative lung disease and bronchiectasis in Alaska Native children. Issue 12 (16th October 2018) - Kinghorn, BreAnna; Singleton, Rosalyn; McCallum, Gabrielle B.; Bulkow, Lisa; Grimwood, Keith; Hermann, Leslie; Chang, Anne B.; Redding, Gregory
Abstract : Introduction: Alaska Native (AN) children from the Yukon Kuskokwim (YK) Delta region have high rates of chronic suppurative lung disease (CSLD), including bronchiectasis. We characterized the clinical progress of an AN adolescent cohort with CSLD/bronchiectasis, and estimated bronchiectasis prevalence trends in this region. Methods: The original cohort comprised 41 AN children (originally aged 0.5‐8 years) with CSLD/bronchiectasis, recruited between 2005 and 2008, with follow‐up in 2015‐2016. Clinical assessments, lung function, radiography, medical chart review, and spirometry were obtained. We also conducted data queries of bronchiectasis diagnoses in YK individuals born between 1990 and 2010 to estimate prevalence. Results: Thirty‐four (83%) of the original cohort aged 7.3‐17.6 years were reviewed, of whom 14 (41%) had high‐resolution computed tomography (HRCT)‐confirmed bronchiectasis, eight (24%) had no evidence of bronchiectasis on HRCT scans, while 12 (35%) had not undergone HRCT scans. Annual lower respiratory tract infection (LRTI) frequency decreased with age, although 27 (79%) still had respiratory symptoms, including all with HRCT‐confirmed bronchiectasis, who were also more likely than those without confirmed bronchiectasis to have recent wheeze (80 vs 25%, P  = 0.005), auscultatory crackles (60 vs 0%, P  < 0.001), and lower mean forced expiratory volume in 1‐second/forced vital capacity ratio (73 vs 79%, P  = 0.03). The bronchiectasis prevalence for YK AN people born during 2000‐2009 was 7 per 1000 births, which was lower than previously reported. Conclusion: Despite reduced LRTI frequency, most AN children with CSLD/bronchiectasis had symptoms/signs of underlying lung disease as they entered adolescence. Close clinical follow‐up remains essential for managing these patients as they transition to adulthood.